Building Surveying Experience of Architecture Students in Safranbolu Tannery using Virtual Reality - Küçükkara, Muhammed Yusuf; Özacar, Kasım; Ortakcı, Yasin (Fırat University, 2024)
Historical buildings damaged due to natural disasters and man-made destruction are restored to have the most similar appearance to their original state. At the same time, architecture students conduct research and gather information on these buildings to learn about the restoration process. However, conditions such as pandemics, diseases, dangers, and adverse weather conditions that restrict accessibility prevent students from accessing these buildings. This study aims to overcome the access difficulties experienced by architecture students during the examination of historical buildings in the restoration courses by utilizing Virtual Reality (VR) and especially to teach the measurement techniques in the restoration course in a virtual environment with remote access. Within the scope of the study, the Historic Safranbolu Tannery Building, whose data collection process was completed before restoration, was modeled with its actual dimensions, and transferred to the VR environment. For students to work together interactively in this building, we implemented virtual versions of traditional measuring tools such as tape measure, water hose, plumb and whiteboard into the system. Thus, unlike other studies in the literature in the field of architectural restoration, a virtual educational environment has been created in which multiple students interact with each other simultaneously as if they were in the same environment, despite being in physically different environments. In the post-experiment questionnaires, it was observed that the participants generally had a positive perspective on the developed method. The system achieved an average score of 88.62% across a comprehensive set of 14 statements within the questionnaire. These findings indicate that VR presents a valuable opportunity for practical training in restoration courses, particularly when face-to-face education is not accessible.

Doğal afetler ve insan kaynaklı tahribatlar sebebi ile zarar gören tarihi yapılar ilk haline en yakın bir görünüme kavuşacak şekilde restore edilmektedir. Aynı zamanda mimarlık öğrencileri bu yapılar üzerinde restorasyon süreçlerini öğrenmek için araştırmalar yapmakta ve bilgi toplamaktadır. Fakat erişebilirliği kısıtlayan pandemi, hastalık, tehlike ve olumsuz hava gibi koşullar öğrencilerin bu yapılara erişmelerini engellemektedir. Bu çalışma, mimarlık öğrencilerinin restorasyon derslerinde tarihi yapıları inceleme sırasında yaşadıkları erişim zorluklarını Sanal Gerçeklik (SG) teknolojisinden faydalanarak gidermeyi ve özellikle öğrencilere uzaktan erişimle, restorasyon dersindeki ölçme tekniklerini sanal ortamda uygulamalı olarak öğretmeyi amaçlamaktadır. Çalışma kapsamında, restorasyon öncesi veri toplama işlemi tamamlanmış olan Tarihi Safranbolu Tabakhane Binası gerçek ölçüleri ile modellenmiş ve sanal gerçeklik ortamına aktarılmıştır. Öğrencilerin bu binada etkileşimli olarak beraber çalışabilmeleri için geleneksel ölçme araçları olan metre, su hortumu, şakül ve yazı tahtasının sanal versiyonları sisteme entegre edilmiştir. Böylece mimari restorasyon alanında literatürde yer alan diğer çalışmalardan farklı olarak, birden fazla öğrencinin fiziksel olarak farklı ortamlarda olmalarına rağmen aynı ortamdaymış gibi eş zamanlı olarak birbirleriyle etkileşimde bulunduğu, sesli ve görsel iletişim kurabildikleri sanal bir eğitim ortamı oluşturulmuştur. Kullanıcı deneyi sonrası yapılan anketlerde, öğrencilerin geliştirilen yönteme genellikle olumlu bakış açısı sergiledikleri ve anketteki toplam 14 ifadenin puanlamasında sistemin %88,62’lik bir puan ortalamasına ulaştığı gözlemlenmiştir. Sonuçlar, sanal gerçekliğin yüz yüze eğitime ulaşımın olmadığı durumlarda, restorasyon derslerine yönelik uygulamalı bir eğitim fırsatı sunduğunu ortaya koymaktadır.
Mimarlık Öğrencilerinin Sanal Gerçeklik Ortamında Safranbolu Tabakhanesinde Rölöve Alma Deneyimi
Keywords: Interactive Narrative; Etkileşimli Anlatım; Virtual and Mixed Reality; Sanal ve Karma Gerçeklik